ketahanan enam klon karet terhadap infeksi CORYNESPORA CASSIICOLA PENYEBAB PENYAKIT GUGUR DAUN - Nurhayati1, Fatma & M. Idrus Aminuddin . (Universitas Lampung, 2010)
Resistance of six rubber clones to Corynespora cassiicola the pathogen of rubber leaf fall disease. The objectives of the research was to evaluate the resistance of six rubber clones to Corynespora cassiicola, the pathogen of rubber leaf fall disease. The research was conducted at Phytophatology laboratorium and green house at the Plant Pest and Diseases Department, Faculty of Agriculture, Sriwijaya University, from March to July 2008. The treatments were arranged in a completely randomized block design (CRBD) with six treatments and four replications. Each replication consisted of four polibags of rubber plants. The clons tested were GT 1, PB 260, IRR 39, BPM 1, BPM 24 and PR 261. The results showed that IRR 39 was the most susceptible clon to C. cassiicola infection, whereas disease severety reach up to 98.45 % and leaf fall 73.95 %. Clon PB 260 show as the moderat resistance clon to the pathogen infection. The severity disease of this clon only 41.53 % and leaf fall 10.41%.